Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Step-by-step explanation:
(f o g)(x)
= f(x² - 5)
= 4(x² - 5) + 1
= 4x² - 19.
Therefore (f o g)(4) = 4(4)² - 19 = 64 - 19 = 45.
Answer:
[tex]\boxed {\boxed {\sf 45}}[/tex]
Step-by-step explanation:
When solving a composition of function composition, work from the inside to the outside.
We have the composition:
- (f o g)(4)
We must start on the inside, and find g(4) first.
1. g(4)
The function for g is:
[tex]g(x)=x^2-5[/tex]
Since we want to find g(4), we have to substitute 4 in for x.
[tex]g(4)=(4)^2-5[/tex]
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Addition, and Subtraction. First we should solve the exponent.
- (4)²= 4*4= 16
[tex]g(4)=16-5[/tex]
Subtract 5 from 16.
[tex]g(4)= 11[/tex]
Now, since g(4) equals 11, we have:
- (f o g)(4)= f(11)
2. f(11)
The function for f is:
[tex]f(x)= 4x+1[/tex]
We want to find f(11), so substitute 11 in for x.
[tex]f(11)= 4(11)+1[/tex]
Solve according to PEMDAS and multiply first.
[tex]f(11)= 44+1[/tex]
Add.
[tex]f(11)= 45[/tex]
(f o g)(4) is equal to 45.
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.